FARABI - THINKER-MATHEMATICIAN, NATURALIST, TEACHER IN MODERN EDUCATION - Balykbayev, Т.О; Bidaibekov, Е.Ы (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2020)
This year, the 1150th anniversary of the great scientist Abu Nasir al-Farabi is widely celebrated. In this regard, it is necessary to especially note the merits of the outstanding researcher of the history and pedagogy of Muslim East science, Professor Audanbek Kubessov, who restored the true image of the great scientist as a thinker-mathematician, naturalist and teacher. His special contribution to science as a scientist is directly related to the study of the research works of the great scientist Abu Nasir al-Farabi. A. Kubesov researched the rich scientific heritage of al-Farabi and published more than two hundred scientific, popular and science and other works, translations from the Arabic language of the great scientist. Our current duty is to use and promote the rich heritage of our ancestor al-Farabi in teaching and educating the youth.